CLASS STUDY ON FLOOD VULNERABILITY LEVELS FOR HYDROLOGICAL DISASTER MITIGATION DIRECTIONS IN THE KRUENG JREUE ACEH BESAR SUB WATERSHED - Eka Sri Wulandari; Helmi (Jurnal Penelitian Progresif, 2023)
The increasing intensity of land conversion in the Krueng Jreue Aceh Besar Sub-watershed from forest to non-forest or due to changes in land use causes changes in the biophysical aspects of the land. Changes in the biophysical aspects of land cause an increase in the level of flood vulnerability. This research uses a descriptive method (survey). The research results show: The variables determining the level of flood vulnerability are based on biophysical aspects of forest and land, namely: dynamic factors (rainfall, land use) and statistical factors (soil infiltration, slope slope). Flood Vulnerability Level Classes (TKB), consisting of: Very Vulnerable, organizations, rice fields (42≤TKB≤50); Vulnerable, moor (34≤TKB≤41); and Medium, open land, shrubs, grasslands, secondary forests, primary forests (26≤TKB≤33), average 32.38 (medium class). Directions for mitigating hydrological disasters in cultivation areas (settlements, rice fields and moors), by implementing flood prevention and air management measures, implementing soil and air conservation and regulating planting patterns. Meanwhile, in non-cultivated areas (open land, bushes, grasslands, secondary forests and primary forests), by implementing land rehabilitation packages and preventing illegal logging.